Dynamic Sliding Mode Control Based on Multi-Model Switching Laws for the Depth Control of an Autonomous Underwater Vehicle. (29th July 2015) - Zhou, Huanyin; Liu, Kaizhou; Li, Yiping; Ren, Shenzhen
This manuscript presents an improved control algorithm, called Dynamic Sliding Mode Control based on Multiple Models Switching Laws (DSMC-MMSL), for the control of the depth of the studied Autonomous Underwater Vehicle (AUV) system, the diving plane controller of which faces disturbances arising from the coupled states. The diving plane model is strongly coupled with the state variables, such as surge speeds and course angles. To achieve the desired dynamic performance, the proposed algorithm consists of two parts: the diving plane control part and the pitch control part, which is used to avoid large pitch angles. Some direct switching control laws are used for the two parts to avoid some impulse phenomena on the control executions. The error-states exponential decay is recommended to eliminate the chattering on the sliding surface. The DSMC-MMSL controller was successfully implemented and experimentally validated with the studied AUV system designed and built by Shenyang Institute of Automation. The results of some lake trials demonstrated that the depth control performances of the AUV system were as desired, and that the AUV system was robust enough for the coupled state variables under the DSMC-MMSL algorithm control.